2016
DOI: 10.3892/etm.2016.3190
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia induces autophagy in cardiomyocytes via a hypoxia-inducible factor 1-dependent mechanism

Abstract: Hypoxia frequently accompanies such vascular disorders as atherosclerosis, thrombosis and ischemia/reperfusion injury. Myocardial ischemia/reperfusion, in particular, is a major contributor to cardiomyocyte impairment. Autophagy is a dynamic, self-catabolic process that has been implicated in a wide range of physiological processes and the pathogenesis of diverse diseases. The aim of the present study was to investigate the promotion of autophagy by hypoxia in a rat H9c2 heart cell line and determine the regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 48 publications
(38 reference statements)
1
32
0
Order By: Relevance
“…BNIP3 is stimulated by hypoxia and induces autophagy by weakening the binding of the Bcl‐2/Beclin1 complex . Hypoxia also induced autophagy by the upregulation of ATG5 and ATG7 . MAC increased BNIP3, Beclin1 and ATG7 expression, and HIF‐1α nuclear translocation (Figure ).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…BNIP3 is stimulated by hypoxia and induces autophagy by weakening the binding of the Bcl‐2/Beclin1 complex . Hypoxia also induced autophagy by the upregulation of ATG5 and ATG7 . MAC increased BNIP3, Beclin1 and ATG7 expression, and HIF‐1α nuclear translocation (Figure ).…”
Section: Discussionmentioning
confidence: 92%
“…10 Hypoxia also induced autophagy by the upregulation of ATG5 and ATG7. 46 MAC increased BNIP3, Beclin1 and ATG7 expression, and HIF-1α nuclear translocation ( Figure 5). The low levels of oxygen and nutrients enhance autophagy signalling in the tumour microenvironment.…”
Section: Discussionmentioning
confidence: 93%
“…It removes dysfunction mitochondria through autophagy selectively, promotes mitochondrial renewal and recycling, and ensures the stability of mitochondrial function, thereby promoting cell survival (Lemasters, 2005;Saito and Sadoshima, 2015). Previous studies have shown that hypoxia-induced mitochondrial autophagy mostly exists as a protective mechanism, and activated relying on autophagy protein (Gui et al, 2016). BNIP3 is a mitochondrial autophagy receptor related to hypoxia, and is a crucial target downstream gene of HIF-1a, which is considered to be an important signaling molecule for hypoxia-induced mitochondrial autophagy (Ney, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Free radicals production are also increased ending in a phase of injury characterized by membrane damage produced by phospholipid loss, lipid peroxidation, and cytoskeletal damage [45]. Other mechanisms include hypoxia-induced hypertrophy accompanied by autophagy, increased hypoxia-inducible factor 1α (HIF-1α) mRNA, and accumulation of HIF-1 protein in nuclei [46,47]. …”
Section: Discussionmentioning
confidence: 99%